6
$\begingroup$

Two well known constants

$$\int_{0}^{\infty}{\ln x\ln\left(x\over 1+x\right)\over (1+x)^2}=\zeta(2)\tag1$$

$$\int_{0}^{\infty}{\ln x\ln\left(x\over 1+x\right)\over 1+x}=\zeta(3)\tag2$$

An attempt:

Applying IBP: $$\int{\ln x\over x}\mathrm dx={1\over 2}\ln^2 x+C\tag3$$

Rewrite $(2)$ as

$$\int{\ln^2 x\over 1+x}\mathrm dx-\int{\ln(x)\ln(1+x)\over 1+x}\mathrm dx=I_1-I_2\tag4$$

Let integrate $I_1$, applying IBP

$$I_1=\ln^2(x)\ln(1+x)-2\int{\ln(x)\ln(1+x)\over x}\mathrm dx\tag5$$

$$I_1=-\ln^2(x)\ln(1+x)+2\ln(x)\ln(1+x)-2\int{\ln(x)\ln(1+x)\over x}\mathrm dx\tag6$$

$I_1$ is not going down any further.

Let try $I_2$ applying IBP

$$I_2={1\over 2}\ln(x)\ln(1+x)+{1\over 2}\int{\ln^2(x)\over x}\mathrm dx\tag7$$

$$\int{\ln^2(x)\over x}\mathrm dx={1\over 3}\ln^3(x)+C\tag8$$

$$I_2={1\over 2}\ln(x)\ln(1+x)+{1\over 6}\ln^3(x)+C\tag9$$

This seem too complicate, what I am doing here

How can we tackle $(1)$ and $(2)$ in a less cumbersome way?

$\endgroup$
10
$\begingroup$

Hint. By the change of variable $$ u=\frac{x}{x+1},\quad du=\frac{dx}{(1+x)^2}, $$ one gets $$ \begin{align} \int_{0}^{\infty}{\ln x\ln\left(x\over 1+x\right)\over (1+x)^2}&=\int_{0}^{1}\left(\ln u - \ln(1-u)\right)\ln u \:du \\\\&=\int_{0}^{1}\ln^2 u\:du - \int_{0}^{1}\ln(1-u)\ln u \:du \\\\&=2 +\sum_{n=1}^\infty \frac1n\int_{0}^{1}u^{n}\ln u \:du \\\\&=2 -\sum_{n=1}^\infty \frac1{n(n+1)^2} \\\\&=2 +\frac{\pi^2}6-2 \\\\&=\zeta(2). \end{align} $$Similarly, one has $$ \begin{align} \int_{0}^{\infty}{\ln x\ln\left(x\over 1+x\right)\over 1+x}&=\int_{0}^{1}\left(\ln u - \ln(1-u)\right)\frac{\ln u}{1-u} \:du \\\\&=\int_{0}^{1}\frac{\ln^2 u}{1-u} \:du - \int_{0}^{1}\frac{\ln(1-u)\ln u }{1-u} \:du \\\\&=2\zeta(3)- \int_{0}^{1}\frac{\ln(1-v)\ln v }{v} \:dv \\\\&=2\zeta(3)-\zeta(3) \\\\&=\zeta(3), \end{align} $$ where we have used some standard results.

$\endgroup$
  • 1
    $\begingroup$ Thank you @Olivier Oloa, you make it looks so simple! I feel like slapping myself. $\endgroup$ – gymbvghjkgkjkhgfkl Apr 12 '17 at 12:46
  • $\begingroup$ Nice! (+1) I think you have an extra minus sign in your formula for $du$. It should be $du=1/(1+x)^2\,dx$, right? $\endgroup$ – mickep Apr 12 '17 at 12:52
  • 1
    $\begingroup$ @mickep Thank you! (edited) $\endgroup$ – Olivier Oloa Apr 12 '17 at 12:54
  • $\begingroup$ You are so fast!+1) $\endgroup$ – xpaul Apr 12 '17 at 14:11
4
$\begingroup$

Splitting the first integral into two and for the second one using $x\to\frac1x$, one has \begin{eqnarray} \int_{0}^{\infty}{\ln x\ln\left(x\over 1+x\right)\over (1+x)^2}dx&=&\int_{0}^{1}{\ln x\ln\left(x\over 1+x\right)\over (1+x)^2}dx+\int_{1}^{\infty}{\ln x\ln\left(x\over 1+x\right)\over (1+x)^2}dx\\ &=&\int_{0}^{1}{\ln x\ln\left(x\over 1+x\right)\over (1+x)^2}dx+\int_{0}^{1}{\ln \frac1x\ln\left(\frac1x\over 1+\frac 1x\right)\over (1+\frac1x)^2}\frac1{x^2}dx\\ &=&\int_{0}^{1}{\ln x\ln\left(x\over 1+x\right)\over (1+x)^2}dx+\int_{0}^{1}{\ln x\ln\left(1+x\right)\over (1+x)^2}dx\\ &=&\int_{0}^{1}{\ln^2 x\over (1+x)^2}dx\\ &=&\zeta(2). \end{eqnarray} Splitting the second integral into two and for the second one using $x\to\frac1x$, one has \begin{eqnarray} \int_{0}^{\infty}{\ln x\ln\left(x\over 1+x\right)\over 1+x}dx&=&\int_{0}^{1}{\ln x\ln\left(x\over 1+x\right)\over 1+x}dx+\int_{1}^{\infty}{\ln x\ln\left(x\over 1+x\right)\over 1+x}dx\\ &=&\int_{0}^{1}{\ln x\ln\left(x\over 1+x\right)\over 1+x}dx+\int_{0}^{1}{\ln \frac1x\ln\left(\frac1x\over 1+\frac 1x\right)\over 1+\frac1x}\frac1{x^2}dx\\ &=&\int_{0}^{1}{\ln x\ln\left(x\over 1+x\right)\over 1+x}dx+\int_{0}^{1}{\ln x\ln\left(1+x\right)\over x(1+x)}dx\\ &=&\int_{0}^{1}{\ln^2 x\over 1+x}dx+\int_{0}^{1}{\frac1x\ln x\ln(1+x)}dx-2\int_{0}^{1}{\ln x\ln\left(1+x\right)\over1+x}dx. \end{eqnarray} It is easy to see that $$ \int_{0}^{1}{\ln^2 x\over 1+x}dx+\int_{0}^{1}{\frac1x\ln x\ln(1+x)}dx=\frac34\zeta(3) $$ by using series. Note \begin{eqnarray} 2\int_{0}^{1}{\ln x\ln\left(1+x\right)\over1+x}dx&=&\ln x\ln^2(1+x)\bigg|_0^1-\int_0^1\frac1x\ln^2(1+x)dx\\ &=&-\frac{1}{4}\zeta(3). \end{eqnarray} So $$ \int_{0}^{\infty}{\ln x\ln\left(x\over 1+x\right)\over 1+x}dx=\zeta(3). $$

$\endgroup$
  • $\begingroup$ Nice answer! (+1) $\endgroup$ – Olivier Oloa Apr 12 '17 at 19:13

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.